2013
DOI: 10.1177/1756283x13504727
|View full text |Cite
|
Sign up to set email alerts
|

The role of capsule endoscopy in acute gastrointestinal bleeding

Abstract: Acute gastrointestinal (GI) bleeding is a common cause of hospitalization, resulting in about 400,000 hospital admissions annually, with a mortality rate of 5-10%. It is estimated that 5% of acute GI bleedings are of obscure origin with a normal esophagogastroduodenoscopy and ileocolonoscopy. Capsule endoscopy is the state-of-the-art procedure for inspection of the entire small bowel with a high sensitivity for the detection of causes of bleeding. In recent years, many studies have addressed the sensitivity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
(33 reference statements)
0
13
0
1
Order By: Relevance
“…(3) The exact prevalence of angioectasias is unclear because most patients are asymptomatic and only 10% of all patients will experience a symptomatic gastrointestinal bleed during their lifetime (13,17,18). (5,7,11) The clinical presentation of angioectasias includes overt bleeding or iron deficiency anemia, which represent the main indications for endoscopic treatment (3,13,19,20). (5,10) Nevertheless, recurrence rates after medical, endoscopic and/or surgical therapy of SBVL remain unclear (10,13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) The exact prevalence of angioectasias is unclear because most patients are asymptomatic and only 10% of all patients will experience a symptomatic gastrointestinal bleed during their lifetime (13,17,18). (5,7,11) The clinical presentation of angioectasias includes overt bleeding or iron deficiency anemia, which represent the main indications for endoscopic treatment (3,13,19,20). (5,10) Nevertheless, recurrence rates after medical, endoscopic and/or surgical therapy of SBVL remain unclear (10,13).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the source of the bleed responsible for OGIB is usually located in the small bowel (2,4). Possible small bowel etiologies of OGIB include angioectasias, erosions and ulcers secondary to Crohn's disease or non-steroidal anti-inflammatory drug use, polyps, tumors, Meckel's diverticulum, varices and Dieulafoy's lesions (5)(6)(7)(8). In Western countries, angioectasias represents the most frequent lesion found during device assisted-enteroscopy (DAE) in patients with OGIB, which is the main indication for this technique (6,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, CE accounts for 56%-70% of small intestinal bleeding disorders [1] , whereas the definite diagnostic yield is only 20%-30% [2,3] . DBE accounts for 60%-70% of the diagnostic yield for intestinal diseases [4,5] .…”
Section: Discussionmentioning
confidence: 99%
“…7 9 88-90 Thrombin injection has been described for gastric variceal bleeding in cohort studies, but to date no RCTs have compared it with other treatments. [91][92][93] Post-endoscopic management PPI therapy A meta-analysis of RCTs comparing PPIs to placebo or no therapy in high risk patients undergoing successful endoscopic therapy showed that high dose PPIs, usually given as an intravenous bolus of 80 mg followed by continuous infusion at 8 mg/h for 72 After resuscitation, transfusion to hemoglobin 70-80 g/L, and correction of coagulopathy, endoscopy was undertaken. (B) Through-the-scope clips were applied after dilute epinephrine was injected into the four quadrants of the ulcer base.…”
Section: Endoscopic Therapy Non-variceal Bleedingmentioning
confidence: 99%